Kommunikáció az esélyegyenlőségi emberi erőforrás menedzsmentben - Dajnoki, Krisztina (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
We spend most of our lifetime working, so it is vital to have such a job which meets all of our expectations. Working this way contributes not only to the creation of our security feeling, but helps to realize ourselves. Moreover, considering the development of economy and society, it is important that we let people work and meet their individual needs through securing adequate number and quality positions. Working chances of changed capacity persons are largely determined by how they are treated, by which aspect, and what kind of information a society access about their life, capacities and objectives. This article aims to introduce, by research results, what communication factors influ-ence the positions of changed capacity potentional employees and how important informa-tion supply and media are in the support of their integration.